2015
DOI: 10.1136/bmjopen-2014-006997
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an emergency nurse practitioner service for adults presenting to rural hospitals with chest pain: protocol for a multicentre, longitudinal nested cohort study

Abstract: IntroductionChest pain is common in emergency department (ED) patients and represents a considerable burden for rural health services. Health services reforms to improve access to care need appropriately skilled and supported clinicians in the delivery of safe and effective care, including the use of emergency nurse practitioners (ENPs). Despite increasing use of ENPs, little is known about the safety and quality of the service in the rural ED context. The aims of this study are (1) to examine the safety and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Sample size calculations were based on the primary outcome for the study and reported in the previously published study protocol [ 36 ]. Using the results from our preliminary study [ 37 ], we anticipated a six-month period for data collection; however, there were critical issues with participant recruitment necessitating termination of the study prior to achieving the requisite sample.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample size calculations were based on the primary outcome for the study and reported in the previously published study protocol [ 36 ]. Using the results from our preliminary study [ 37 ], we anticipated a six-month period for data collection; however, there were critical issues with participant recruitment necessitating termination of the study prior to achieving the requisite sample.…”
Section: Methodsmentioning
confidence: 99%
“…Using the results from our preliminary study [ 37 ], we anticipated a six-month period for data collection; however, there were critical issues with participant recruitment necessitating termination of the study prior to achieving the requisite sample. Data analysis was performed according to the pre-published analysis plan [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Nurse practitioners have a direct role in improvement of risk stratification and timely reperfusion. 25,26 Better risk assessment increases inclusion in secondary prevention and rehabilitation programmes targeting lifestyle changes and pharmaceutical therapy. Furthermore, an updated and shared STEMI protocol, use of checklists, and oral and written discharge instructions could improve documentation and prescription of discharge medication.…”
Section: Discussionmentioning
confidence: 99%
“…This includes the capability to assess, diagnose and treat; initiate referrals to other health care workers; request and interpret diagnostic tests; prescribe and review medications and discharge [ 12 – 14 ]. These skills and competencies are important in the delivery of safe and effective health care in a rural UCC, such as timely assessment and initiation of chest pain management [ 15 ] and the clinical capability to see and treat all presentations from mild through to high acuity [ 11 ]. Despite being introduced in Australia in 2000, the NP-led model of care has yet to realise its full potential as a legitimate option for addressing workforce needs in rural health care delivery [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%